Comparing nurse practitioners/physician assistants and physicians in diagnosing pediatric abdominal pain for ESI level 3 patients seen in the emergency department. Issue 2 (18th February 2022) - Hoyt, Karen Sue; Agan, Donna L.; Jordan, Kathleen Sanders; Ramirez, Elda; Nichols, Stephen; Topp, Robert
Abstract : Background: Accuracy of emergency department (ED) diagnosis affects care management including tests, discharges, and readmissions. Purpose: This retrospective study compared nurse practitioners/physician assistants (NPs/PAs) with physicians (MDs/DOs) on accuracy of diagnosing Emergency Severity Index (ESI) level 3 pediatric abdominal pain (AP) in the ED. Abdominal pain unrelated to trauma is a common ED pediatric visit. Methodology: Data acquired from four hospital sites of a multistate emergency group examined patients younger than 18 years who were initially admitted for AP ESI level 3. Results: The accuracy of AP ESI level 3 diagnoses was 94.9%, 90.9%, and 96.5% by physicians, NPs/PAs, and a collaboration of NP/PA/physician, respectively (χ 2 = 13.187, p < .001). Accuracy of AP ESI level 3 diagnoses was greater with general admissions, intensive care unit admissions, transfers, or left against medical advice (100%) than with those who were discharged (χ 2 = 11.058, p = .001). Abdominal pain complaints were segmented into five areas (i.e., AP, back pain, chest pain, epigastric pain, and pelvic pain). Irrespective of provider, those with a final diagnosis of AP or epigastric pain were correctly triaged and those with a final diagnosis of chest or back pain were incorrectly triaged as AP ESI level 3. Conclusions: When comparing providers in this subset ( n = 43), there was no significant difference in the accuracy of assigning AP ESI level 3 (χ 2 = 0.467, p = .495). Implications: Only cases with a final diagnosis of pelvic/genitourinary pain saw disparity in the accuracy (27 correct, 16 incorrect, χ 2 = 1, 681.80, p < .001).